Utilization of Available Facilities of Computer Aided Teaching in Secondary Level School of Nepal - Giri, Bhimsen; Dhakal, Megha Raj (Journal of Advanced Academic Research, 2018)
Computer aided teaching is modern technical teaching practice which is gradually replacing the traditional teaching practice by using the blackboard, chalk and duster. Nepalese secondary level schools are also gradually practicing the computer aided teaching system. The growing completion of private boarding school also compels to manage such modern facilities to attract the students. The facilities are comparatively weak in public school because the public school depends on the government funding. The study measured the utilization practice of available facilities of computer aided teaching in secondary level school. The study was conducted in Dang and Pyuthan district of Nepal. In total 578 students were selected from the different schools of two district by using the simple random sampling. The result shows that there was significant (p = .019) different between the students of two districts regarding their practice to spend the total days in a week in computer lab, use of internet in school and types of computer users whereas there was no difference in use of computer in leisure time and facility of soft copy of reading materials provided by school. The comparatively, computer and internet use practice is found better in Dang district than the Pyuthan though in totality, the result of computer aided teaching practice is not satisfactory. So, the concerned authority of public and private school of both districts should enhance the capacity of management and teachers to maximize the facilities of computer aided teaching practice in Nepal.